2020
DOI: 10.22190/fupes200614035d
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Spinal Postural Disorders in First-Grade Elementary-School Students

Abstract: The aim of this study is to determine the state of postural disorders in the sagittal and frontal planes of the spinal column, as well as any gender differences in first-year elementary school students. The participant sample comprised 138 school children, 73 male and 56 female participants, all from the territory of the municipality of Knjaževac, Serbia. The measuring instrument, the Formetric 4D System, Diers, Germany was used for the assessment of postural disorders of the spinal column. The testing results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…We also verified whether the size of spinal curvatures is related to the values of demographic or somatic variables. The previous studies (Wojtys et al, 2000;Stošić et al, 2011;Sanz-Mengibar et al, 2018) showed a positive correlation between LL and TK with the length of training experience, but in acrobatic gymnasts, such a relation was not found. There was only a weak positive correlation between the length of training experience and the size of the SS in both sexes.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We also verified whether the size of spinal curvatures is related to the values of demographic or somatic variables. The previous studies (Wojtys et al, 2000;Stošić et al, 2011;Sanz-Mengibar et al, 2018) showed a positive correlation between LL and TK with the length of training experience, but in acrobatic gymnasts, such a relation was not found. There was only a weak positive correlation between the length of training experience and the size of the SS in both sexes.…”
Section: Discussionmentioning
confidence: 70%
“…A review of the scientific literature does not indicate clearly whether competitive practice in sport has a positive or negative impact on the shape of the spine. Some studies indicate that practiced sports don't determine spinal shape in a relax standing position (Muyor et al, 2013;López-Miñarro et al, 2017), while others show that the sagittal curvature of the spine can gradually adapt to the sport played if training is conducted intensively over a long period of time (Wojtys et al, 2000;Stošić et al, 2011;Sanz-Mengibar et al, 2018). Some predominantly "feminine" sport such as gymnastics, are characterized by an extremely large range of motion (ROM), and due to the repetitive flexion, extension, and rotation, gymnasts are particularly at risk for spine overloads (Kums et al, 2007;Stošić et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of postural disorders was conducted using the Formetric 4D System (Diers, Schlangenbad, Germany), a non-invasive diagnostic tool that employs photom-etry [18][19][20]. Previous research has confirmed its validity and reliability [21,22].…”
Section: Variables For the Evaluation Of The Postural Status In The S...mentioning
confidence: 99%